2004
DOI: 10.1037/0735-7044.118.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Amphetamine Hypophagia: A Real-Time Depiction of Learning to Suppress Stereotyped Movements in the Rat.

Abstract: To analyze how tolerance develops to amphetamine-induced hypophagia, the authors recorded real-time licking responses in rats given chronic injections of the drug and access to milk for 30 min. Initially, licking was greatly reduced and occurred only late in the session. The acquisition of tolerance was characterized by a decrease in the latency to initiate licking, a gradual increase in the number of licks, and a reorganization of the temporal licking pattern such that licks were distributed throughout the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…By the end of tolerance training, rats in the 0-h group expressed a robust tolerance to cocaine suppressive effects, self-administering sucrose with the same performance and efficiency as the control group. As predicted by Wolgin et al (Wolgin, 2000;Wolgin and Hertz, 1995;Wolgin and Jakubow, 2004), this tolerance only developed when rats had access to sucrose while intoxicated by cocaine. Although we did not observe tolerance learning in 1-h rats across repeated choice sessions, a partial extinction of tolerance occurred in some 0-h rats, in agreement with prior research (Woolverton et al, 1978).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…By the end of tolerance training, rats in the 0-h group expressed a robust tolerance to cocaine suppressive effects, self-administering sucrose with the same performance and efficiency as the control group. As predicted by Wolgin et al (Wolgin, 2000;Wolgin and Hertz, 1995;Wolgin and Jakubow, 2004), this tolerance only developed when rats had access to sucrose while intoxicated by cocaine. Although we did not observe tolerance learning in 1-h rats across repeated choice sessions, a partial extinction of tolerance occurred in some 0-h rats, in agreement with prior research (Woolverton et al, 1978).…”
Section: Discussionsupporting
confidence: 57%
“…Previous research showed that tolerance can be induced in hungry rats when amphetamine or cocaine is administered immediately before access to food (Wolgin, 2000;Wolgin and Hughes, 1997;Woolverton et al, 1978). This tolerance is called contingent tolerance because its development requires that animals experience the suppressive effects of the drug while they are eating, or at least, trying to (Wolgin, 2000;Wolgin and Jakubow, 2004). Indeed, if animals are no longer under the influence of amphetamine or cocaine when given access to food, all else being equal, they do not develop tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…In simplified terms, this means that the dissipation of such effects is not merely the result of the repeated presence of the drug but of adaptive appetitive and consummatory behavior that develops in response to the repeated presence of the drug while reward is retrieved and consumed (Hughes et al 1998; Wolgin 2002; Wolgin and Jakubow 2004). Thus, locomotor hyperactivity, stereotyped behavior, and the anorexic effects of repeated AMPH exposure are not observed in animals that learned to perform tasks in the presence of AMPH.…”
Section: Repeated Amphetamine Exposure As An Animal Modelmentioning
confidence: 99%
“…Previous research showed that a tolerance to drug-suppressive effects can be learned in hungry rats when amphetamine or cocaine is administered immediately before access to food (Wolgin 2000;Wolgin and Hughes 1997;Woolverton et al 1978). This tolerance is an active learning process called "contingent tolerance" because its development does not result from passive drug exposure but instead requires that animals experience the suppressive effects of the drug while they are eating or, at least, trying to (Wolgin 2000;Wolgin and Jakubow 2004). Indeed, if animals are no longer under the influence of amphetamine or cocaine when given access to food, all else being equal, they do not develop tolerance and drastically suppress food intake when tested under drug influence.…”
Section: Introductionmentioning
confidence: 99%